Musculoskeletal disorders among dentists and dental students in West Sumatera, Indonesia - Abu Bakar; Rifani Rifani; Valendriyani Ningrum; Shih C. Lee (Journal of Dentomaxillofacial Science, 2019)
Objectives: The purpose of this study is to describe the prevalence of musculoskeletal disorders (MSDs) in dentist and dental students in West Sumatera.Materials and Methods: The study design was cross-sectional with 261 samples by using total sampling technique. The instrument was Nordic Body Map (NBM) questionnaire and Cornell Musculoskeletal Discomfort Questionnaires (CMDQ).Results: Some anatomical body parts were indicated to have a high prevalence in experiencing musculoskeletal disorders. They were waist (55%), right shoulder (49%), upper neck (48%), right wrist (45%), and lower neck (42%), respectively. The quality of the pain was varied.Conclusion: The high prevalence of MSDs may cause by static postures and the big force needed by certain body parts during the dental treatment.Â